PENDIDIKAN ANAK USIA DINI PERSPEKTIF AL-QUR’AN DAN PSIKOLOGI - Ainul Churria Almalachim; Nailul Fauziyah; Asep Maulana (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2020)
This paper is a paper that uses literature review with the theme of the concept of Educating Children from the Quranic perspective, by using the concept of literal interpretation, the results of this paper are that the success of children's educational processes in the family is very dependent on the roles and responsibilities of the family itself. Where parents as the core of the family has a very important role, it is he who is fully responsible for the educational process of children in the family, so that it can be said that the success of the child's educational process in the family is very dependent on how parents carry out their duties and responsibilities. The implication of the meaning of wisdom for educator figures is that an educator in addition to constantly trying to improve his academic abilities, he also tries to harmonize with his practice. Paper ini adalah paper yang menggunakan kajian pustaka dengan tema konsep Mendidik Anak Perpektif al Quran, dengan menggunakan konsep interpretasi literal, hasil paper ini adalah Keberhasilan proses pendidikan anak dalam keluarga sangat tergantung pada peran dan tanggung jawab keluarga itu sendiri. Di mana orang tua sebagai inti dari keluarga memiliki peranan yang sangat penting, dialah yang bertanggung jawab penuh terhadap proses pendidikan anak dalam keluarga, sehingga dapat dikatakan bahwa keberhasilan proses pendidikan anak dalam keluarga sangat tergantung pada bagaimana orang tua melaksanakan tugas dan tanggung jawabnya tersebut. Implikasi dari makna hikmah bagi figur pendidik adalah bahwa seorang pendidik selain senantiasa berusaha meningkatkan kemampuan akademiknya, ia pun berupaya menselaraskan dengan amalannya.